Trademarks as a telecommunications indicator for industrial analysis and policy - Mendonça, S. (Telecommunication economics: Selected results of the cost action IS0605 Econ@Tel, 2012)
Innovation and economic transformation are difficult phenomena to measure, especially in high-tech fast changing sectors. Dynamic competition is a key driving force behind growth and a complex, multidimensional nature calls for an integrated approach. Recently a research agenda that see trademark as a valuable addition to the economic indicators arsenal has been gaining momentum. This section makes the case for employing trademarks as an indicator for assessing dynamic competition and international competitiveness in the telecommunications equipment and services sector. It considers community trademark data to explore stylized facts and recent trends in the European market, a sophisticated and contested world sales pitch on which this data can be employed to generate substantive academic insights as well as useful knowledge for policy-makers at the EU and national levels.